Broadcast Writing: Principles and Practice - Walters, Roger L. (New York McGraw-Hill, Inc., 1988)
For people who are interested in broadcasting and wish to learn more skills in evaluating their own work. Information on analyzing real situations and how to best write about them.
Keywords: Writing